Social capital among oil palm independent smallholders in Johor, Malaysia - Sahidan, Ainul Shazwin (2018)
This study was undertaken to investigate the existing and contribution of the social capital element towards the fresh fruit bunch (FFB) production among independent smallholders (ISH) in Johor. Social capital is a broad term containing the social networks and norms that generate shared understandings, trust, and reciprocity, which underpin cooperation and collective action for mutual benefits, and creates the base for economic prosperity. Qualitative approached was used to understand the situation or phenomenon through interview and observation from different point of view. There were three types of informants including independent smallholders (ISH) who have high and low FFB production from the same study area, extension agents and the authorized person in the village. Convenient sampling was used according to preselected criteria that relevant to a particular research questionwith triangulation data collection method. The finding showed that independent smallholders with good operation of social capital revealed a positive relationship towards FFB production among oil palm independent smallholders. It also facilitates as an information exchange platform, influence in decision making and problem solving and work effectiveness. As for the recommendation; (1) built up the awareness regarding the importance of social capital among independent smallholders (2) the responsible body could provide more agricultural programme that related to the smallholders in order to increase the oil palm productivity and (3) extension agent need to empower their competency and effectiveness in order to understand the unique characteristic that describes their clientele.